2018
DOI: 10.1097/qai.0000000000001652
|View full text |Cite
|
Sign up to set email alerts
|

Finding Hidden HIV Clusters to Support Geographic-Oriented HIV Interventions in Kenya

Abstract: Background:In a spatially well known and dispersed HIV epidemic, identifying geographic clusters with significantly higher HIV prevalence is important for focusing interventions for people living with HIV (PLHIV).Methods:We used Kulldorff spatial-scan Poisson model to identify clusters with high numbers of HIV-infected persons 15–64 years old. We classified PLHIV as belonging to either higher prevalence or lower prevalence (HP/LP) clusters, then assessed distributions of sociodemographic and biobehavioral HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In Siaya, clusters of higher new HIV diagnoses were found in areas around specific towns, around major roads, near a major road intersection and adjacent to a beach. Although geospatial clustering of new HIV diagnoses has not yet been described in the literature, other studies have described the clustering of higher HIV prevalence [ 10 , 13 ] and incidence [ 12 ] around similar ecological factors. The clustering around ecological features observed in our study suggests that population-level factors related to the ecological features, including socioeconomic, mobility and geographic factors, may influence the clustering of new HIV diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…In Siaya, clusters of higher new HIV diagnoses were found in areas around specific towns, around major roads, near a major road intersection and adjacent to a beach. Although geospatial clustering of new HIV diagnoses has not yet been described in the literature, other studies have described the clustering of higher HIV prevalence [ 10 , 13 ] and incidence [ 12 ] around similar ecological factors. The clustering around ecological features observed in our study suggests that population-level factors related to the ecological features, including socioeconomic, mobility and geographic factors, may influence the clustering of new HIV diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding individuallevel characteristics that could be associated with HIV testingseeking behavior is equally important. For example, using a household level survey, Waruru et al found that economic status, perception of HIV risk, mobility, transactional sex, and uncircumcised men were associated with living in high HIV prevalence clusters in Kenya (8).…”
Section: Precision Targetingmentioning
confidence: 99%
“…Previous analysis of population-based household survey data in Kenya has shown that clusters of high rates of HIV infections may exist even in low burden counties (8). Examining the HIV burden without regard to arbitrary physical boundaries that may confine populations by ethnicity, culture, human settlements, and natural resources provides an opportunity for equitable resource allocation.…”
Section: Introductionmentioning
confidence: 99%
“…Faria et al used the HIV-1 sequence data from Central Africa and reconstructed the early stage of HIV-1 transmission history; they emphasized that both social changes and transport networks played important roles in the viral establishment in human populations [39]. The geospatial viral migration patterns and temporal dynamics of HIV-1 transmission can be further reconstructed when molecular network analysis is combined with both geographical and temporal information [35,40,41]. A study on the HIV-1 epidemic in the Nordic countries found both different HIV-1 transmission patterns between countries and linkages in a large geographical region; Denmark and Sweden showed the strongest geographical link, and Denmark had a great part of heterosexual domestic spread of HIV-1 subtype B [32].…”
Section: Molecular Network Reconstruct the History Of Hiv Spreadmentioning
confidence: 99%